Promoting Students’ Well-Being and Inclusion in Schools Through Digital Technologies: Perceptions of Students, Teachers, and School Leaders in Italy Expressed Through SELFIE Piloting Activities - Panesi, Sabrina; Bocconi, Stefania; Ferlino, Lucia (Frontiers in Psychology, 2020)
Digital technology in its various forms is a significant component of our working environment and lifestyles. However, there is a broad difference between using digital technologies in everyday life and employing them in formal education. Digital technologies have largely untapped potential for improving education and fostering students’ well-being and inclusion at school. To bring this to fruition, systemic and coordinated actions involving the whole school community are called for. To help schools exploit the full range of opportunities digital technologies offer for learning, the European Commission has designed and implemented a self-reflection tool called SELFIE (Self-reflection on Effective Learning by Fostering Innovation through Educational Technology). Based on the DigCompOrg conceptual framework, SELFIE encompasses key aspects for effectively integrating digital technologies in school policies and practices. The present study investigates how SELFIE can also support the school community to self-reflect about students’ well-being and inclusion. In Italy, the SELFIE online questionnaire has been completed by 24,715 students, 5,690 teachers and 1,507 school leaders, for a total of 31,912 users from 201 schools (at primary, lower secondary and upper secondary levels) located in ten different regions. The complementary data we have collected regarding student well-being and inclusion highlight significant differences in the perceptions on this issue reported by students, teachers and school leaders. These findings have important implications for facilitating successful practices within the whole school community in order to promote students’ well-being and inclusion using educational technologies, as well as for planning future actions following a systemic approach.